Analysis of consumption expenditures and determining factors of rice availability for households of lebak rice farmers in Kertapati District, Palembang - Yunita Yunita; Riswani Riswani; Selly Oktarina (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2025)
Meeting nutritional needs is crucial for developing quality human resources, while food security depends on production capacity, purchasing power, and supply chain factors, influenced by socio-economic and ecological conditions. The research aimed to analyze the total income of farmer households, analyze the consumption expenditure of farmer households, and analyze the factors that influence the availability of rice for households of lowland rice farmers in Kertapati District, Palembang City. The research method used was a survey method. This research was carried out in July 2024 with a total of 50 samples selected simply at random.  The data processing method used to answer the first and second objectives is mathematical calculations to calculate rice farming income, non-rice farming income and non-farming income, as well as calculating food and non-food consumption expenditure. Meanwhile, to answer the third objective, multiple linear regression analysis was used. The results of this research showed that: 1) The average total household income of Lebak rice farmers was 4,457,241 IDR/month. 2) household food consumption expenditure for Lebak rice farmers was 2,674,626 IDR/month, while non-food consumption expenditure was 1,594,396,- IDR/month. 3). The availability of rice for lowland rice farmers' households is 2.65 kg/month, which was included in the low criteria.  Factors that influence the availability of rice for Lebak rice farming households were land area, income and age of the farmer. Land area and income has a positive effect, while farmer age has a negative effect.